Raman and white light spectroscopy/imaging studies of graphene - Wang, Yingying (2011)
In this thesis, the Raman/white light spectroscopy and imaging are used to probe electronic, vibrational and optical properties of graphene samples fabricated by two common methods, micromechanical exfoliation (ME) of highly oriented pyrolitic graphite (HOPG) method or epitaxial growth method.